1995
DOI: 10.1144/gsjgs.152.2.0269
|View full text |Cite
|
Sign up to set email alerts
|

Silurian turbidites used to reconstruct a volcanic terrain and its Mesoproterozoic basement in the Irish Caledonides

Abstract: The Lettergesh Formation, Co. Galway, Ireland, comprises a 1.5 km thick sequence of turbidites deposited c. 430 Ma ago during closure of the Iapetus Ocean. Petrographic and geochemical data show that the turbidites consist overwhelmingly of detritus derived from a young volcanic terrain. Palaeocurrent data indicate that the detritus was derived from the north. Modelling of the chemical compositions of the turbidites indicates provenance from a high-K calc-alkaline, subduction-related vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The Lettergesh sandstones have a significant detrital volcanic component. It has been suggested that the rapid deposition of such a thick sedimentary succession was related to a major volcanic episode near the basin at this time (Williams, O'Connor & Menuge, 1992;Menuge, Williams & O'Connor, 1995). The deposition of the sandstones resulted in the accumulation of some 1300 m (compacted) of sediment between the uppermost Llandovery and the Lower Wenlock, possibly over two to three million years.…”
Section: Conglomerates and Sea-level Variationmentioning
confidence: 96%
“…The Lettergesh sandstones have a significant detrital volcanic component. It has been suggested that the rapid deposition of such a thick sedimentary succession was related to a major volcanic episode near the basin at this time (Williams, O'Connor & Menuge, 1992;Menuge, Williams & O'Connor, 1995). The deposition of the sandstones resulted in the accumulation of some 1300 m (compacted) of sediment between the uppermost Llandovery and the Lower Wenlock, possibly over two to three million years.…”
Section: Conglomerates and Sea-level Variationmentioning
confidence: 96%
“…The much simpler east trending upright folding of the Silurian rocks of the Killary Harbour area (Menuge, Williams & O'Connor, 1995) and faulting, with small displacements (up to 1 km) across the Doon Rock and Salrock faults contrasts with the fault-controlled higher strains and up to biotite grade in the Silurian rocks of the Clew Bay area.…”
Section: Tectonic History Of the Silurian Rocksmentioning
confidence: 98%
“…Silurian rocks rest unconformably upon this sequence. A recent study has shown them to be derived from a young volcanic arc to the north (Menuge, Williams & O'Connor, 1995) and they are not discussed further here. The Ards Peninsula and the Cavan-Monaghan area of the Longford-Down massif are both part of the Central Terrane and contain elements of both the Northern (Ordovician) and Central (mainly Silurian) belts of Southern Uplands stratigraphy.…”
Section: Introductionmentioning
confidence: 97%